230k views
2 votes
4(2x-3)+8(x-4)=2(2x+6) help plzzz

2 Answers

3 votes

Answer:


x=(14)/(3)

Explanation:


4(2x-3)+8(x-4)=2(2x+6)

Expand parentheses:


8x-12+8x-32=4x+12

Combine similar terms:


16x-44=4x+12

Subtract 4x and add 44 to both sides:


12x=56

Divide both sides by 12:


x=(14)/(3)

Hope this helps!

User Erangad
by
5.2k points
5 votes

Answer:

x = 14/3

Explanation:

4(2x-3)+8(x-4)=2(2x+6)

Distribute

8x -12 +8x - 32 = 4x +12

Combine like terms

16x -44 = 4x+12

Subtract 4x

16x-4x -44 = 4x+12-4x

12x -44 =12

Add 44 to each side

12x-44+44 = 12+44

12x = 56

Divide each side by 12

12x/12 = 56/12

x = 14/3

User JChat
by
5.4k points